DESIGN AND DEVELOPMENT OF TRANSITION AUTOPILOT FOR VTOL UAV - ASWINI KUMAR PATRA,; KANDARP PATEL ,; GOURAV SINGH BUNDELA,; VINAY. P , (International Journal of Innovations in Engineering Research and Technology, 2021)
UAV becomes versatile in nature in terms of application and its compact operation. UAV has its own limits by its design nature. Fixed wing vehicles have high endurance and range where as multi-copter have hovering andvarious terrain operation. This briefs attempts to blend the combination of both fixed-wing and multi-copter and develops autonomous for transition. The conceptual design made with 1kg payload, 1km range, and 16 minute endurance with VTOL capability. The airframe is selected based on the requirements. The propulsion system designed such a way to adopt hover as well as cruise mode operation. The centre of gravity is fixed such a way to maintain during cruise, hover as well as transition. The autopilot is developed for smooth transition of hover to cruise and cruise to hover.